Dad's Old Photo Book - Jay Dale (Oxford, United Kingdom Capstone Global Library Ltd, 2019)
Dad is looking for his old photo book. Will Etta help him look for it?
Keywords: PY-UOI - Where we are in Place and Time -- PY-UOI - Where we are in Place and Time